Molecular Attributes Associated With Refolding of Inclusion Body Proteins Using the Freeze–Thaw Method - Singhvi, Priyank; Verma, Juhi; Panwar, Neha; Wani, Tabiya Qayoom; Singh, Akansha; Qudratullah, Md.; Chakraborty, Arnab; Saneja, Ankit; Sarkar, Debi P.; Panda, Amulya K. (Frontiers in Microbiology, 2021)
Understanding the structure–function of inclusion bodies (IBs) in the last two decades has led to the development of several mild solubilization buffers for the improved recovery of bioactive proteins. The recently developed freeze–thaw-based inclusion body protein solubilization method has received a great deal of attention due to its simplicity and cost-effectiveness. The present report investigates the reproducibility, efficiency, and plausible mechanism of the freeze–thaw-based IB solubilization. The percentage recovery of functionally active protein species of human growth hormone (hGH) and L-asparaginase from their IBs in Escherichia coli and the quality attributes associated with the freeze–thaw-based solubilization method were analyzed in detail. The overall yield of the purified hGH and L-asparaginase protein was found to be around 14 and 25%, respectively. Both purified proteins had functionally active species lower than that observed with commercial proteins. Biophysical and biochemical analyses revealed that the formation of soluble aggregates was a major limitation in the case of tough IB protein like hGH. On the other hand, the destabilization of soft IB protein like L-asparaginase led to the poor recovery of functionally active protein species. Our study provides insight into the advantages, disadvantages, and molecular–structural information associated with the freeze–thaw-based solubilization method.